Biophysics of Cold Adaptation and Acclimatization. - Laursen,Gary A (1977)
The Animal Research Facility at the Naval Arctic Research Laboratory (NARL), provides scientists with logistic support and unique opportunities to study Arctic mammals maintained in an Arctic environment. During FY 77 in-house, visiting and field research projects resulted in 3500 man-hours of support of work conducted by scientists. Research was conducted in the areas of: Comparative thermoregulation; cold adaptation; cold acclimatization; social hierarchy; growth responses to seasonal changes in climatic conditions; water balance; regional heterothermy; heat exchange; radio telemetry (rates and temperatures); threshold tolerances to cold; and ecological studies. Thirteen Arctic mammal species, all native to Alaska's high Arctic North Slope, were used in the experiment. Major improvements were completed at the facility and new techniques for handling the animals were developed through squeeze caging.